THE ROLE OF DIGITAL PEDAGOGY IN DEVELOPING 21st CENTURY SKILLS IN SECONDARY EDUCATION (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This article examines the transformative role of digital pedagogy in fostering 21st century skills among secondary school students. As education systems worldwide adapt to technological advancements and the demands of the digital age, integrating digital tools and methods into pedagogy has become essential